On the purification and preliminary crystallographic analysis of isoquinoline 1-oxidoreductase from Brevundimonas diminuta 7 - Boer, D. Roeland (2005)
Isoquinoline 1-oxidoreductase (IOR) from Brevundimonas diminuta is a mononuclear molybdoenzyme of the xanthine-dehydrogenase family of proteins and catalyzes the conversion of isoquinoline to isoquinoline-1-one. Its primary sequence and behaviour, specifically in its substrate specificity and lipophilicity, differ from other members of the family. A crystal structure of the enzyme is expected to provide an explanation for these differences. This paper describes the crystallization and preliminary X-ray diffraction experiments as well as an optimized purification protocol for IOR. Crystallization of IOR was achieved using two different crystallization buffers. Streak-seeding and cross-linking were essential to obtain well diffracting crystals. Suitable cryo-conditions were found and a structure solution was obtained by molecular replacement. However, phases need to be improved in order to obtain a more interpretable electron-density map.